Matemática aplicada às escolhas sociais: um protótipo para decisões justas - Fagundes, Isabelle Pinheiro (Universidade Federal Rural do Semi-Árido, 2019)
The dissertation evidences the meanings attributed by deaf teachers who work in Higher Education to the act of teaching Libras. The general objective is to analyze the meanings that deaf teachers attribute to teaching in the graduationcourse in Libras Letters from their (auto) biographical narratives, and as specific objectives, to investigate which experiences marked and / or mark the trajectories of deaf teachers who act in the graduation course in Libras Letters; to identify, from the (auto) biographical narratives, relevant elements to think about the process of teaching Libras as first and second language by deaf teachers; to reflect on the graduation course in Libras Letters as a place of empowerment and professional emancipation of the deaf subject from the (auto) biographical narratives. What do deaf teachers tell us about their formation trajectory and their teaching practices? This questioning guides the methodological course that has its assumptions in the (Auto) Biographical Research in Education. The corpus used for analysis consists of five signaled narrative interviews and, later, translated and transcribed. Five deaf teachers from the Federal University of Rio Grande do Norte took part in the course. The sources were collected during the year 2018, by means of narrative interviews suggested by Jovchelovicth and Bauer (2002) and adapted to meet the linguistic specificities of the collaborators. The (auto) biographical narratives allowed the teachers of Libras, firstly, to reflect and narrate about their educational trajectories, from the entrance to the regular school to the arrival at the university; later, reflect and narrate about relevant elements in the process of teaching Libras. The analysis of the signaled narratives revealed to us that the family, whether of a kinship or a cultural tie, play an essential role in the emotional, social and educational support in the life of the deaf person. The school does not present itself as a positive memory of learning, of cognitive, academic and social development, but reminiscent of hostile times. Already the university brings a memory of hope, of opportunity, dignity, social and academic interaction, cognitive, socio-affective, cultural and identity development. They also revealed that Libras has an immeasurable political and cultural value for the deaf, and is still the most democratic, viable and legal way for the social, cognitive and academic advancement of the deaf, from schooling to arrival and staying in the labor market. The Libras course is a symbol of the empowerment, emancipation and pride of the deaf people, it is a place of visibility of the language and its users, where teachers can reflect and apply their teaching methods that are diverse, respecting the differences in the process of teaching Libras to deaf as L1 and to listeners like L2. Finally, our collaborators perceive the meaning of teaching as an act of resistance, political, ideological, cultural and emancipatory, for until a given moment in history they did not even have the right to life, and in time they gained some rights. Of all the rights achieved, the most important for them is to have an official language, disseminated, studied and taught
Keywords: Professores surdos; Narrativas autobiográficas; Ensino de LIBRAS; Deaf teachers; Autobiographical narratives; Teaching of LIBRAS; CIENCIAS EXATAS E DA TERRA::MATEMATICA